Cervical Inclination Angle: Normative Values in an Adult Multiethnic Asymptomatic Population - Jean Charles Le Huec; Zeeshan M. Sardar; Emanuele Quarto; Meghan Cerpa; Michael P. Kelly; Kazuhiro Hasegawa; Hwee Weng Dennis Hey; Hee-Kit Wong; Hend Riahi; Lawrence G. Lenke; Stéphane Bourret (Neurospine, 2022)
Objective The role of the craniocervical complex in spinal sagittal alignment has rarely been analyzed but it may play a fundamental role in postoperative mechanical complications. The aim of the study is to analyze the normative value of the cervical inclination angle (CIA) in an adult asymptomatic multiethnic population. Methods Standing full-spine EOS of adult asymptomatic volunteers from 5 different countries were analyzed. The CIA was analyzed globally and then in each decade of life. Different ethnicities were compared. Comparisons between different groups was performed using a t-test and statistical significance was considered with a p-value < 0.05. Results EOS of 468 volunteers were analyzed. The global mean CIA was 80.2° with a maximum difference of 9° between T1 and T12 (p < 0.001). The CIA remains constant until 60 years old then decreases significantly passing from a mean value before 20 years old of 82.25° to 73.65° after 70 years old. A statistically significant difference was found between the Arabics and other ethnicities with the formers having an inferior CIA: this was related to a mean older age (p < 0.05) and higher body mass index (p < 0.05) in the Arabics. Conclusion The CIA remains constant until 60 years old and then reduces slightly but never under 70°. This angle is helpful to evaluate the lever arm at the upper instrumented vertebra after an adult spinal deformity surgery and could predict the occurrence of a proximal junctional kyphosis when its value is lower than normal. Further clinical studies must confirm this theory.